(3QSGdI aj BOGH GdHMK hGdefGXQIs - (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s ((3eOQSI GdQHY GdQTjOi s)
(3ChdgG (B:s
(3gPg QSGdI ai GdHMK hGdefGXQI bO cGf ef YGOI GdGbOejf JQJjH cJHge GdefWbjI HEjQGO bSe GdLOd hdeG UGQ Yde GdNdGa ai ReGffG eZfjkG Yfg abO GhOYJ ecGfg bGfhfkG ai GOGH GdHMK hJQJjHg s
(3BNQgG (B:s
(3bhdfG dh EfJbi LejY GdGTjGA jdRe KHhJ GdeOYi hgh eMGd Mdg jeKd eG eQ GP dGjdRe ef YOe EfJaGA LejY GdGTjGA Ydi gPG GdJbOjQ MJi jfYcS HYcS GdfbjVjf hgPG BNQ GdeZGdWGJ ef JUGfja Gdehdi TeS GdedI hGdOjf GdSeQbfOi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B63s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs